Religious Propaganda: Speech by Sjafruddin Prawiranegara During the Emergency Government of the Republic of Indonesia - Sulthan Jiyad Muqsith Asmara; Neni Efrita (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study examines how propaganda in Sjafruddin Prawiranegara’s speech through Radio YBJ-6 functioned as an effective political communication strategy of PDRI during the 1948 crisis, focusing on religious messaging, moral persuasion, and narrative framing to sustain resistance and governmental legitimacy. Theoretical framework: The analysis is based on political communication, propaganda, and framing theories that emphasize persuasive messaging, crisis communication, and symbolic legitimacy within emergency political contexts. Literature review: The review discusses Propaganda Theory, PDRI historical studies, religious messaging in nationalist movements, and radio broadcasting as a wartime communication medium. Methods: Using a qualitative literature-based approach and content analysis, data were collected from historical documents, PDRI archives, and prior research. Analysis followed Miles and Huberman’s stages with a within-case method to identify thematic and persuasive elements. Results: The study finds that Sjafruddin’s propaganda effectively mobilized the military and civilians through religious narratives, moral contrast with Dutch aggression, and calls for unity. Despite a limited communication infrastructure, Radio YBJ-6 successfully reached domestic and international audiences, sustaining morale and legitimacy. Implication: The research highlights the strategic use of religious-moral narratives and radio communication in maintaining state continuity and influencing public sentiment during crises. Novelty: This study proposes a religious-moral propaganda framing model that explains PDRI’s hybrid use of spiritual rhetoric, nationalist appeal, and political legitimacy in a constrained communication environment.